Design, Analysis and Application of Magnetless Doubly Salient Machines - Lee, Christopher H. T. (Springer Theses, Recognizing Outstanding Ph.D. Research, 2018)
This thesis investigates the key characteristics of magnetless doubly salient machines, evaluates their design philosophies, and proposes new topologies for various applications. It discusses the background of and previous research on magnetless machines, while also outlining upcoming trends and potential future developments. The thesis begins by presenting various torque-improving structures - namely the multi-tooth structure, the double-rotor (DR) structure, the axial-field (AF) structure, and the flux-reversal (FR) structure - for magnetless machines. It subsequently addresses the idea of merging the design philosophies of two different machines to form new dual-mode machines. Thanks to a reconfigured winding arrangement and controllable DC-field excitation, the proposed machines can further extend their operating range to meet the extreme demands of applications in electric vehicles and wind power generation. Lastly, the thesis employs the finite element method (FEM) to thoroughly analyze the proposed machines' key performance parameters and develops experimental setups to verify the proposed concepts.